2007
DOI: 10.1016/j.jaci.2007.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Repeat organic dust exposure–induced monocyte inflammation is associated with protein kinase C activity

Abstract: Targeting PKC and specific mediators associated with repetitive organic dust exposure may result in novel therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
46
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 29 publications
6
46
1
Order By: Relevance
“…29 Our findings in this study are also consistent with other studies and our previous studies demonstrating that the endotoxin component in swine barn dust does not completely explain the immune inflammatory response in cultured airway epithelial cells and monocytes. [6][7][8] It appears then that gram positive bacterial components may be the driving component of the organic dust-induced responses observed in our study, but LPS + PGN together most closely mimicked the observations we observed with ODE, suggesting that combinations of biological agents are important in real life exposures. However, it would be an oversimplification to state that a TLR2 and/or TLR4 agonist completely explains the effect observed with organic dust as we did not observe any modulation in TLR2 and TLR4 cell surface expression with organic dust conditioning.…”
Section: Discussionsupporting
confidence: 85%
“…29 Our findings in this study are also consistent with other studies and our previous studies demonstrating that the endotoxin component in swine barn dust does not completely explain the immune inflammatory response in cultured airway epithelial cells and monocytes. [6][7][8] It appears then that gram positive bacterial components may be the driving component of the organic dust-induced responses observed in our study, but LPS + PGN together most closely mimicked the observations we observed with ODE, suggesting that combinations of biological agents are important in real life exposures. However, it would be an oversimplification to state that a TLR2 and/or TLR4 agonist completely explains the effect observed with organic dust as we did not observe any modulation in TLR2 and TLR4 cell surface expression with organic dust conditioning.…”
Section: Discussionsupporting
confidence: 85%
“…Measurement of BALF components including immune cells, microbial/host protein content, cytokines and chemokines, is the method of choice for elevating airway and lung inflammation (Elizur et al, 2008;Sagel et al, 2009). This is consistent with findings reported by Poole et al (2007) where acute exposure to dust induces an inflammatory response demonstrated by secretion of proinflammatory cytokines; however, re-stimulation resulted in a diminished response. This observation may be explained by phenomena termed chronic inflammation adaptation response (Sundblad et al, 2009;May et al, 2012) in which repetitive dust exposure yields a less severe response in agriculture workers compared to naïve subjects.…”
Section: Discussionsupporting
confidence: 84%
“…We have previously found, in vitro, that single exposure to this dust induces significant secretion of proinflammatory mediators (TNF␣, IL-6, IL-8) in human epithelial cells and monocytes/macrophages, and that this response is, in part, regulated through PKC activity, particularly the PKC␣ and PKCε isoforms (31,32). In addition, repeat dust exposure results in an adaptation/ tolerance response in human monocytes (31), and repetitive dust exposure impairs the differentiation and function of macrophages derived from monocytes (30). However, the mechanisms underlying this apparent modulated inflammatory response to single vs. repetitive dust exposures in vivo are not clear.…”
mentioning
confidence: 99%